In Management of Enterprises in the Service Market: Method of Evaluation of Efficiency of Services (Texas Journal of Multidisciplinary Studies, 2022)
The methods used in evaluating services in this article.In evaluating services we recommended evaluating service-oriented investments i.e scientifically substantiating the possibility of increasing the economic efficiency of an enterprise by separating services from the main type of activity and increasing the investment efficiency of services.